A complex rearrangement between APC and TP63 associated with familial adenomatous polyposis identified by multimodal genomic analysis: a case report - Oda, Satoyo; Ushiama, Mineko; Nakamura, Wataru; Gotoh, Masahiro; Tanabe, Noriko; Watanabe, Tomoko; Odaka, Yoko; Aoyagi, Kazuhiko; Sakamoto, Hiromi; Nakajima, Takeshi; Sugano, Kokichi; Yoshida, Teruhiko; et al. (Frontiers in Oncology, 2023)
Genetic testing of the APC gene by sequencing analysis and MLPA is available across commercial laboratories for the definitive genetic diagnosis of familial adenomatous polyposis (FAP). However, some genetic alterations are difficult to detect using conventional analyses. Here, we report a case of a complex genomic APC-TP63 rearrangement, which was identified in a patient with FAP by a series of genomic analyses, including multigene panel testing, chromosomal analyses, and long-read sequencing. A woman in her thirties was diagnosed with FAP due to multiple polyps in her colon and underwent total colectomy. Subsequent examination revealed fundic gland polyposis. No family history suggesting FAP was noted except for a first-degree relative with desmoid fibromatosis. The conventional APC gene testing was performed by her former doctor, but no pathogenic variant was detected, except for 2 variants of unknown significance. The patient was referred to our hospital for further genetic analysis. After obtaining informed consent in genetic counseling, we conducted a multigene panel analysis. As insertion of a part of the TP63 sequence was detected within exon16 of APC, further analyses, including chromosomal analysis and long-read sequencing, were performed and a complex translocation between chromosomes 3 and 5 containing several breakpoints in TP63 and APC was identified. No phenotype associated with TP63 pathogenic variants, such as split-hand/foot malformation (SHFM) or ectrodactyly, ectodermal dysplasia, or cleft lip/palate syndrome (EEC) was identified in the patient or her relatives. Multimodal genomic analyses should be considered in cases where no pathogenic germline variants are detected by conventional genetic testing despite an evident medical or family history of hereditary cancer syndromes.